(untitled) (Journal of Geography and Environmental Management, 2018)
There are considered modern environmental, economic and social problems of the planet Earth for which solution the concept of “sustainable development” has been developed. Evolution of views of “sustainable development” is presented in details. It is shown that the previous Millennium development goals have allowed to save millions of lives and to improve quality of life of billions, but have kept unequal achievements and defects in many spheres. The Agenda of sustainable development until 2030 unites the global purposes in area of development and environmental sustainability in one concept. The main values of 2030 Agenda are listed also 17 sustainable development goals (SDG) which became result of joint work of the international organizations, such as UN, UNESCO and others are formulated. It is shown that human behaviour has led to environmental crises. This paper reviews three of the most common explanations: overpopulation, modern lifestyle and individual behaviour. During 1950-2015 the population of Earth has increased three times that is a serious demographic problem. The correct policy creation of human behaviour is necessary. For example, consumption of resources can be determined by the indicator of an ecological footprint based on calculation of the used land and water resources. Quality education for sustainable development is important. Meeting the SDGs means that all people in low and high income countries have to contribute in their own ways to ensure environmental sustainability for all and for prosperity of the planet future.